2009
DOI: 10.1128/jcm.01524-08
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Distribution, and Origins of Streptococcus pneumoniae Serotype 6C, a Recently Recognized Serotype

Abstract: The prevalence of Streptococcus pneumoniae serotype 6C, a recently recognized serotype that cross-reacts serologically with serotype 6A, was investigated. Isolates of serotype 6A in various collections were recovered, and serotype 6C was differentiated from 6A by multiplex PCR of DNA extracts by using appropriate primers. Antimicrobial susceptibility was performed by Clinical and Laboratory Standards Institute broth microdilution, and selected isolates were typed by pulsed-field gel electrophoresis, repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
52
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 28 publications
(30 reference statements)
14
52
2
1
Order By: Relevance
“…The presence of 8 STs found among only 27 serotype 6C isolates in this study are consistent with other studies that have described a high degree of genetic diversity among this serotype (Campos et al, 2009;Carvalho et al, 2009;Green et al, 2011;Jacobs et al, 2009;Nunes et al, 2009;Rolo et al, 2011b). Of the 8 STs of serotype 6C isolates reported in this study, 4 (1390, 1379, 473, and 1292) have been previously associated with serotype 6A.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The presence of 8 STs found among only 27 serotype 6C isolates in this study are consistent with other studies that have described a high degree of genetic diversity among this serotype (Campos et al, 2009;Carvalho et al, 2009;Green et al, 2011;Jacobs et al, 2009;Nunes et al, 2009;Rolo et al, 2011b). Of the 8 STs of serotype 6C isolates reported in this study, 4 (1390, 1379, 473, and 1292) have been previously associated with serotype 6A.…”
Section: Discussionsupporting
confidence: 81%
“…Two major lineages accounted for 66% of these isolates (CC473 and CC460). Similar findings have been reported by Jacobs et al (2009) who found that among their serotype 6A isolates, the majority were STs 473, 460, 395, and 376. In the Carvalho et al (2009) study, 4 STs (1292, 473, 395, and376) were observed with ST376, accounting for approximately 30% of serotype 6As, including the majority of isolates fully resistant to penicillin and the majority of erythromycin-resistant isolates.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations